Case Report: A novel strategy of endoscopic full-thickness resection: single traction combined with pre-clamping - Jinguo Liu; Jing Xu; Li Wang; Xiaojiang Gu; Xuesong Zhang; Zhou Zhang; Chi Zhang; Liangliang Yu (Frontiers in Medicine, 2025)
Endoscopic full-thickness resection (EFTR) is an effective, economical, and minimally invasive technique for submucosal tumors (SMTs). However, technical complexity and prolonged operative time remain significant limitations. This study introduces a refined EFTR strategy termed “single traction combined with pre-clamping” in a cohort of 10 patients. The proposed technique demonstrates reduced procedural duration, technical difficulty, and intraoperative risks compared to the conventional approach.